Gratification needs factors for authentic self- expression on Instagram - Pei, Zhang; Bolong, Jusang; Sern, Tham Jen; Osman, Mohd. Nizam (HRMARS, 2024)
Research shows that individuals on Facebook and Instagram are more likely to express their authentic personalities rather than idealized ones. The more authentic the self-expression, the higher the life satisfaction. This article needs to investigate the relationship between gratification needs and authentic self-expression in the Instagram context. This online survey study used a comprehensive purposive sampling method, respecting the characteristics of the respondents to suit the purpose of the study. A total of 450 questionnaires were distributed online. The findings suggest that the more positive the need for recognition, the higher the authentic self-expression. All the gratification needs (social needs, motivation needs, communication needs, recognition needs) contribute around 23.1% to making authentic self- expression. This result suggests that Instagram users express themselves more authentically on the media platform when they are actively engaged in platform interactions, such as enhancing personal identity, value, respect, support and creating a sense of belonging.